Factors Associated With Blood Pressure Of Adult Clients - Malinti, Evelin; Elon, Yunus; Wulandari, Imanuel Sri Mei (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
An individual's health status can be reflected in blood pressure. Many factors can affect blood pressure. Thisstudy aims to evaluate risk factors for blood pressure in adults in Cihanjuang Rahayu village. With a crosssectional approach, this study was conducted on a total of 120 respondents selected by purposive sampling.Filling out questionnaires and measuring height and weight, and blood pressure were performed to obtaindata in this study. More than half of respondents have blood pressure above normal which is classified aselevated and hypertension. Socio-demographic data such as age and marital status have a significantrelationship with systolic and diastolic blood pressure (p <.05). Educational level and occupation weresignificantly associated with systolic blood pressure (p <.05). While the level of income has a significantrelationship with diastolic blood pressure (p <.05). Body Mass Index with systolic and diastolic blood pressurehas a significance value of p <.05. There was no significant relationship (p> .05) between activity level, stresslevel, smoking, drinking coffee, sex, and family history with blood pressure. Conducting a healthy lifestyle isvery important to instill in the community to prevent and control high blood pressure.